Enhancing Biology Students' Learning Outcomes through Microlearning at Universitas Nias Raya - Yan Piter Basman Ziraluo (Jurnal Pendidikan Biologi Undiksha, 2025)
The increasing demand for innovative pedagogical approaches in higher education, particularly in the complex domain of science, has led to the use of Kemmis and McTaggart's Classroom Action Research model in this study. This study empirically evaluates the effectiveness of microlearning as a learning strategy to improve the learning outcomes of Biology Education students at Universitas Nias Raya. The intervention was carried out through the application of microlearning modules focused on photosynthesis material, integrated with Script-type cooperative learning through a planned cycle that included the stages of planning, implementation, observation, and reflection. Data collection was carried out through tests, observations, interviews, questionnaires, and documentation; then, it was analyzed using descriptive statistics and qualitative thematic analysis. The results of the study showed a significant and sustained increase in student engagement and academic achievement in each learning cycle; learning completeness increased from 86.11% in cycle I to 97.22% in cycle II. Students showed a very positive response to the implementation of microlearning, especially in terms of motivation, responsibility, and understanding of complex concepts. The integration of digital media and cooperative learning also encouraged a deeper conceptual understanding and strengthened interactions between students in the classroom. This study emphasizes the importance of sociocultural context and local technological conditions in the implementation of microlearning interventions, which have been proven to support increased relevance and effectiveness of learning. These findings enrich theoretical and practical insights while proving that microlearning is an adaptive and effective pedagogical tool in higher education, especially in resource-limited environments. It is recommended that microlearning be integrated into the biology education curriculum to encourage student-centered learning, sustained engagement, and improved academic outcomes. Further research is needed to examine the long-term impact and adaptation of the model in a broader educational context.